Modeling of the Potential Effect of Revaccination against Whooping Cough in Children Aged 6–7 and 14 years within the Framework of the National of preventive vaccinations - N. I. Briko; A. Ya. Mindlina; I. V. Mikheeva; L. D. Popovich; A. V. Lomonosova (Эпидемиология и вакцинопрофилактика)
Relevance. Currently, the national calendar of preventive vaccinations does not provide for revaccination against whooping cough in children over the age of 18 months. At the same time, the epidemiological and economic feasibility of revaccination against whooping cough in children aged 6–7 years, as well as adolescents, has been demonstrated in world practice. Aim. Based on a mathematical model, develop a forecast of pertussis morbidity dynamics and assess the potential socio-economic damage under the current and expanded vaccine prophylaxis algorithms.Methods. Mathematical modeling of the potential effect of revaccination against whooping cough in children aged 6–7 years (scenario 1) and at 6–7 years and 14 years (scenario 2) was carried out within the framework of the national calendar of preventive vaccinations. A simulation dynamic mathematical model is constructed that allows predicting the development of the epidemiological process of whooping cough on the basis of the dynamics of the main indicators of its prevalence in the population that developed in previous years. The model took into account dynamic changes in the preventive effectiveness of vaccinations and the potential level of underestimation of morbidity. The obtained arrays of indicators served as the basis for extrapolating trends in morbidity and mortality until 2034.The calculation of epidemiological benefits was carried out in the metrics of prevented loss of years of life under the two scenarios under consideration in comparison with the current vaccination algorithm. The calculation of the economic effect was carried out on the basis of the obtained indicators of epidemiological benefits in the metrics of the monetary equivalent of the average cost of a year of life, taking into account the projected inflation coefficients until 2034.Results. The projected decrease in the number of years of life lived in a state of illness, in comparison with the current situation, will total 44.5 thousand years for the period 2019–2034 under scenario 1 and 66.7 thousand years under scenario 2. The socio-economic damage from prevented cases of the disease, expressed in the monetary equivalent of the average cost of living, will decrease by 28.6% (scenario 1) or 42.0% (scenario 2).Conclusions. A comparison of the received public benefits with the costs of vaccination shows that the expansion of the NCPP with additional revaccinations against whooping cough (at 6–7 years or at 6–7 and at 14 years) is advisable both in epidemiological and economic aspects.